Going Off Grid: Modeling an Automated Record Search to Process Electronically Reported Reactive Nontreponemal Syphilis Tests. Issue 10 (October 2018) - Matthias, James; Keller, Gayle; Cha, Susan; Wilson, Craig; Peterman, Thomas A.
Abstract : Background: Before searching prior records, sexually transmitted disease programs use syphilis reactor grids to exclude some reactive nontreponemal test results (RNTs) based on patient age, gender, and test titer. We propose a new algorithm that starts with comparing RNTs to previous syphilis nontreponemal tests and current treponemal test results. Methods: Deduplicated RNTs from Florida's surveillance system (2006–2015) were extracted and stratified on morbidity. An algorithm was developed to triage RNTs. Sensitivity and specificity of the algorithm and the current reactor grid were estimated using reported syphilis cases. A random sample of cases missed by the proposed algorithm, stratified by stage of disease, was reviewed to verify case classification. Results: Reported RNTs increased 58% from 2006 (n = 34, 808) to 2015 (n = 55, 001) (total = 372, 902). The current reactor grid removed 91, 518 (24.5%) RNTs and missed 1149 potential cases. Strictly following the reactor grid would result in a sensitivity of 97.4% and a specificity of 27.5%. The proposed algorithm would remove 242, 078 (64.9%) RNTs and miss 2768 potential cases. This results in a slightly lower sensitivity of 93.8%, but nearly triples the specificity, 72.9%. A review of a random sample of the 2768 cases estimated that 72.7% would not have met the syphilis surveillance case definition, resulting in an adjusted sensitivity of 98.4%. Conclusions: In Florida, an algorithm that starts by searching previous syphilis test results vastly improved specificity and slightly improved sensitivity compared with the current reactor grid. Implementing an automated algorithm could increase case ascertainment efficiency and further prioritize likely cases for investigation. Abstract : An automated algorithm for processing nontreponemal laboratory results would greatly improve syphilis surveillance efficiency compared with traditional reactor grids.